The effectiveness of normative messages to decrease meat consumption: The superiority of dynamic normative messages framed as a loss - De Groot, Judith Irene Maria (Frontiers in Sustainability, 2022)
Consumer behaviors related to food consumption, such as meat consumption, is acknowledged to be a main contributor to the environmental problems. Recent research supports the efficacy of normative messages to change these behaviors for the good. Normative messages make the social norm salient in the behavioral context. Research shows that the normative messages are effective to encourage “desired” pro-environmental behavior if this behavior is carried out by a numerical majority. However, the pro-environmental consumer behaviors are often carried out by a minority of people only. Making salient these behaviors performed by minority of people in normative messages often backfires because the normative message makes salient that it is normal to perform the “undesirable” environmentally harmful behavior. To overcome this shortfall, research has experimented with highlighting that the desired behavior, although still a behavior by minority people, has increased in prevalence (i.e., a dynamic rather than static normative message). However, when such dynamic normative messages are most effective is less clear. Specifically, according to goal-framing theory, it can be assumed that a dynamic normative message highlighting that an increasing minority of people start carrying out the desirable behavior represents a gain frame, while emphasizing that the behavior performed by majority of people is decreasing indicates a loss frame. So far, research on dynamic normative messages only applied gain frames in their messages. This is surprising, as construal level theory (CLT) suggests that the dynamic normative messages will be more effective when framed as a loss. This study therefore tested whether a dynamic normative message is more effective than a static normative message or no message at all, depending on whether it is framed as a loss or a gain. In a one-way between-subject experimental design, including five experimental conditions [i.e., static descriptive normative message (1) gain framed or (2) loss framed; dynamic descriptive normative message (3) gain framed or (4) loss framed; (5) control condition; N = 270], we found that only dynamic normative messages that were framed as a loss were more effective in encouraging a consumer's intention to reduce meat consumption. Therefore, the dynamic normative messages are effective to encourage pro-environmental consumer behaviors of minority of people, but especially when they are framed as a loss rather than a gain.